The Role Of The Legal Department Of The Regional Secretariat In The Establishment Of Local Legal Products - Rini Andriani; Rakhmat Bowo Suharto (Jurnal Hukum Khaira Ummah, 2021)
The purpose of this researchknow and analyze the roleThe Legal Division of the Tegal Regency Regional Secretariat in the formation of regional legal products within the Tegal Regency Government. The approach method used by the author in this research is a normative juridical approach, with a descriptive analytical research specification. The conclusion obtained in this study is that the role of the Legal Section of the Secretariat of Tegal Regency through the formation of regional legal products gets a very good predicate, while the inhibiting factors are the lack of human resources and the absence of structured and massive training for Legislation Subdivision Staff and Functional Positions. Legislators, and lack of interest due to the difficulty of getting credit points for promotions.